2003
DOI: 10.1021/bi034803l
|View full text |Cite
|
Sign up to set email alerts
|

PA1b, an Insecticidal Protein Extracted from Pea Seeds (Pisum sativum):  1H-2-D NMR Study and Molecular Modeling,

Abstract: PA1b (pea albumin 1, subunit b) is a 37-amino acid cysteine-rich plant defense protein isolated from pea seeds (Pisum sativum). It induces short-term mortality in several pests, among which the cereal weevils Sitophilus sp. (Sitophilus oryzae, Sitophilus granarius, and Sitophilus zeamais) that are a major nuisance for stored cereals, all over the world. As such, PA1b is the first genuine protein phytotoxin specifically toxic to insects, which makes it a promising tool for seed weevil damage control. We have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
58
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 50 publications
(61 reference statements)
3
58
0
Order By: Relevance
“…Except for these homologues, the sequence of this protein does not share any similarity with those of other known toxins. The three-dimensional structure, resolved from the extracted peptide (9), shows that PA1b adopts a typical knottin fold with a triple-stranded antiparallel ␤-sheet and three buried interlocked disulfide bonds, a signature of the inhibitory cystine knot family (10,11). The ring embedded in the structure, through which the third disulfide bond threads, is composed of eight residues.…”
mentioning
confidence: 99%
“…Except for these homologues, the sequence of this protein does not share any similarity with those of other known toxins. The three-dimensional structure, resolved from the extracted peptide (9), shows that PA1b adopts a typical knottin fold with a triple-stranded antiparallel ␤-sheet and three buried interlocked disulfide bonds, a signature of the inhibitory cystine knot family (10,11). The ring embedded in the structure, through which the third disulfide bond threads, is composed of eight residues.…”
mentioning
confidence: 99%
“…The three-dimensional structure resolved from the extracted peptide shows that PA1b adopts a typical knottin fold with a triple-stranded antiparallel ␤-sheet and three buried interlocked disulfide bonds, the signature of the inhibitory cystine knot (ICK) 2 family (8). The ICK motif is present in a large number of fungal, plant, and animal peptides and provides them with proteolytic, thermal, and chemical stability.…”
mentioning
confidence: 99%
“…Although responsible for a wide range of biological activities (9), ICK peptides are mainly voltage-gated ion channel blockers when extracted from animals and enzyme inhibitors when they are of plant origin (10). Structural analyses have also revealed similarities between PA1b and the ICK atracotoxin ACTX-Hi: OB4219, which is isolated from the insectivorous Australian funnel-web spider Hadronyche infensa and which targets an unknown channel (8,11).…”
mentioning
confidence: 99%
“…Poth et al (11) present evidence supporting a gradual evolutionary path, whereby the albumin-1 chainb slowly evolved into a more stable cyclotide domain. For example, the pea albumin-1 subunit-b (PA1b), one of the best-studied Fabaceae albumin components, is a 37-aa peptide from pea seeds (Pisum sativum), which also contains a cystine-knot structure (13). Remarkably, the cystine-knot core of PA1b overlays extremely well with that of the cyclotide Cter M. The composition and size of the PA1b loops are, however, totally different from those of the cyclotide Cter M. Recent mutagenesis studies on PA1b have also recently shown that this albumin domain is highly tolerant to mutations outside the cystine knot core (14).…”
mentioning
confidence: 99%
“…As indicated by Poth et al (11), the structural analysis of PA1b may reveal some clues about how this could have happened. The NMR structure of PA1b (13) reveals that the N and C termini are very close to each other, and it is possible that mutations in the albumin genes predisposed them to cyclization during the evolution process.…”
mentioning
confidence: 99%